The search for a melanoma-tailored chemotherapy in the new era of personalized therapy: a phase II study of chemo-modulating temozolomide followed by fotemustine and a cooperative study of GOIM (Gruppo Oncologico Italia Meridionale) - Guida, Michele (BMC Cancer, 2018)
BACKGROUND: It is frequently asked whether chemotherapy can still play a role in metastatic melanoma considering the effectiveness of the available drugs today, including antiCTLA4/antiPD1 immunotherapy and antiBRAF/antiMEK inhibitors. However, only approximately half of patients respond to these drugs, and the majority progress after 6–11 months. Therefore, a need for other therapeutic options is still very much apparent. We report the first large trial of a sequential full dose of fotemustine (FM) preceded by a low dose of temozolomide (TMZ) as a chemo-modulator in order to inactivate the DNA repair action of O(6)-methylguanine DNA-methyltransferase (MGMT). Primary endpoints were overall response and safety. We also evaluated specific biological parameters aiming to tailor these chemotherapies to selected patients. METHODS: A total of 69 consecutive patients were enrolled. The main features included a median age of 60 years (21–81) and M1c stage, observed in 74% of the patients, with brain metastases in 15% and high LDH levels in 42% of the patients. The following schedule was used: oral TMZ 100 mg/m(2) on days 1 and 2 and FM iv 100 mg/m(2) on day 2, 4 h after TMZ; A translational study aiming to analyse MGMT methylation status and base-excision repair (BER) gene expression was performed in a subset of 14 patients. RESULTS: We reported an overall response rate of 30.3% with 3 complete responses and a disease control rate of 50.5%. The related toxicity rate was low and mainly of haematological types. Although our population had a very poor prognosis, we observed a PFS of 6 months and an OS of 10 months. A non-significant correlation with response was found with the mean expression level of the three genes involved in the BER pathway (APE1, XRCC1 and PARP1), whereas no association was found with MGMT methylation status. CONCLUSION: This schedule could represent a good alternative for patients who are not eligible for immune or targeted therapy or whose previous therapies have failed. TRIAL REGISTRATION: EUDRACT 2009–016487-36l; date of registration 23 June 2010. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4479-2) contains supplementary material, which is available to authorized users.